Array of bis-quaternary ammonium surfactant tailored Cu(2−x)Te quantum dots with amended functional assets. Issue 17 (2nd February 2016) - Jamwal, Deepika; Rana, Dolly; Pathak, Dinesh; Raizada, Pankaj; Thakur, Pankaj
Abstract : Copper telluride [Cu(2− x ) Te] nanoparticles stabilized by highly hydrophobic surfactants were synthesised and their structural, optical and electrical properties were examined. Abstract : Building on previous work, many studies have focussed on metal chalcogenide nanomaterials for diverse applications such as photothermal ablation of tumor cells and photothermal therapy, etc. Despite the large amount of related work, the available literature suggests that the size-dependent morphological impacts and similar characteristics have not been proposed for the aforementioned variety of chalcogenides. Explicitly, we present a simple synthetic pathway for the synthesis of copper telluride [Cu(2− x ) Te] nanoparticles (NPs) stabilized by highly hydrophobic surfactants. The structural, optical and electrical properties were examined in relation to the cumulative diameter of the copper telluride NPs using various surfactants. Transmission electron micrography (TEM) suggests the increasing hydrophobic character of the surfactants is a factor for the morphological changes in the copper telluride NPs. Electrical conductivity studies of copper telluride nanoparticles were carried out at room temperature. The current–voltage ( I – V ) curves are linearly symmetric towards the origin inferring that the contacts are ohmic and the resistance of the samples is in the range from 1–5 Ω. UV-vis spectroscopy gave optical band gap values of 3.42 eV, 3.40 eV and 3.37 eV for the (12-2-12), (14-2-14) and (16-2-16) capped copper telluride NPs, respectively. A change in the band gap with diameter demonstrates a blue shift, which may be attributed to a quantum size effect in the NPs. Broadening of the photoluminescence (PL) peak may suggest strain amongst the nanoparticles instigated by size induced quantization effects.